Crown ether-based poly (aryl-dimethyl piperidone) salt anion exchange membrane and preparation and application thereof
By introducing crown ether groups into the anion exchange membrane to form a hydrogen ion-crown ether complex, the degradation problem of the existing membrane under alkaline conditions is solved, and the high OH-conductivity, mechanical properties and service life are improved.
Patent Information
- Application Number
- CN202411847154.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
AI Technical Summary
When existing anion exchange membranes operate under acidic conditions, they have poor alkali stability and are susceptible to OH-attack, resulting in reduced membrane performance and shortened service life.
The poly(aryl-dimethylpiperidone) salt based on crown ether is used as the material for the anion exchange membrane, and the hydrogen ion-crown ether complex is formed by introducing crown ether groups into the polymer framework, thereby improving the alkali stability and mechanical properties of the membrane.
The OH-conductivity, mechanical strength and dimensional stability of the anion exchange membrane are significantly improved, the service life of the membrane is extended, and the high stability is maintained under alkaline conditions.
Smart Images

Figure CN119751788A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ion exchange membranes, in particular to a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane and the preparation and application thereof. Background Art
[0002] At present, proton exchange membrane fuel cells and acidic electrolyzers operating under acidic conditions require the use of precious metal catalysts and expensive proton exchange membranes, which makes hydrogen production costs too high and greatly hinders industrial development. Anion exchange membrane fuel cells and alkaline water electrolysis technologies can use low-alkaline electrolytes and non-precious metal catalysts to reduce operating costs, and therefore have received widespread attention.
[0003] Anion exchange membrane (AEM) can separate hydrogen and oxygen produced by water electrolysis, while allowing the transport of hydroxyl ions and water molecules, balancing the charges and reactants required for oxygen evolution reaction and hydrogen evolution reaction on the anode and cathode electrodes, respectively. AEM is composed of a polymer skeleton, cationic groups and mobile ions. The properties of the polymer main chain structure and cationic groups directly determine the performance of AEM. The research on AEM currently still faces the following technical bottlenecks: (1) OH in AEM - The conductivity is low, and the most direct way to improve the conductivity is to increase the ion exchange capacity (IEC). The increase in IEC means the introduction of more hydrophilic cationic groups, which leads to increased water absorption and swelling of the membrane, thus causing a decrease in the mechanical properties of the membrane. Therefore, solving the "trade-off" effect between the ionic conductivity and dimensional stability of the membrane is crucial to the development of AEM. (2) Under hot alkaline working conditions, the polymer skeleton and cationic groups are susceptible to nucleophilic OH - The attack by ions causes complex degradation reactions of the main chain structure and cationic groups, which degrades the membrane performance and even reduces the service life of the AEM.
[0004] Therefore, it is very important to provide an anion exchange membrane that can solve the above technical problems. Summary of the invention
[0005] In order to solve the above problems, the purpose of the present invention is to provide a crown ether-based poly (aryl-dimethyl piperidone) salt anion exchange membrane and its preparation and application. Compared with the existing anion exchange membrane, the crown ether-based poly (aryl-dimethyl piperidone) salt anion exchange membrane provided by the present invention has improved alkali stability and extended membrane service life.
[0006] Crown ether polymers can react with K +Ionic complexes are considered to be common polymer scaffolds in the field of host-guest chemistry and are used to make supramolecular assemblies and ion sensors. In AEM applications, the ether bonds in the crown ether group are alkali-stable and can form hydrogen ion-crown ether complexes to increase water absorption and accelerate OH - conduction, but the crown ether structure has relatively good alkaline stability, which improves the OH - The density can alleviate the degradation of the membrane under alkaline conditions.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] The first object of the present invention is to provide a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane, which is composed of a compound having a structure shown in formula (I) (containing two polymer segments of poly(dibenzocrown ether-methylpiperidone) salt and poly(terphenyl-methylpiperidone) salt):
[0009]
[0010] Here, x is any integer from 1 to 99.
[0011] The second object of the present invention is to provide a method for preparing a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane, comprising the following steps:
[0012] (S1) dissolving dibenzo-18-crown-6, p-terphenyl, N-methyl-4-piperidone, trifluoromethanesulfonic acid and trifluoroacetic acid in dichloromethane, mixing and reacting, and post-treating to obtain a crown ether-based poly(aryl-methylpiperidone);
[0013] Among them, the structural formula of the crown ether-based poly(aryl-methylpiperidone) is shown in formula (II):
[0014]
[0015] Here, x is any integer from 1 to 99.
[0016] (S2) dissolving the crown ether-based poly(aryl-methylpiperidone) prepared in step (S1) in DMSO, then mixing with methyl iodide and reacting, and post-treating to obtain a crown ether-based poly(aryl-dimethylpiperidone) salt;
[0017] (S3) dissolving the crown ether-based poly(aryl-dimethylpiperidone) salt prepared in step (S2) and casting it into a film, and then post-treating it to obtain a self-supporting polymer film;
[0018] (S4) placing the self-supporting polymer membrane prepared in step (S3) in a KOH solution for ion exchange, and washing to obtain a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane.
[0019] In one embodiment of the present invention, in step (S1), the molar ratio of dibenzo-18-crown-6 to p-terphenyl is 0-10:10-0;
[0020] The molar ratio of the sum of the added amounts of dibenzo-18-crown-6 and p-terphenyl to the added amount of N-methyl-4-piperidone is 1:0.9-1.2;
[0021] The molar ratio of N-methyl-4-piperidone to the trifluoroacetic acid is 1:0.8-1.2;
[0022] The molar ratio of the N-methyl-4-piperidone to the trifluoromethanesulfonic acid is 1:8-12.
[0023] In one embodiment of the present invention, in step (S1), the reaction process is under the protection of an inert atmosphere, the temperature is 0 to 10° C., and the time is 6 to 15 hours.
[0024] In one embodiment of the present invention, in step (S1), the post-processing is specifically as follows:
[0025] The reactant was precipitated in 1 mol / L NaOH solution (immersed at 60° C. for 12 h to neutralize excess acid), then washed with deionized water to neutrality, and dried under vacuum at 60° C. to obtain a white solid: crown ether-based poly(aryl-methylpiperidone).
[0026] In one embodiment of the present invention, in step (S2), the mass ratio of the crown ether-based poly(aryl-methylpiperidone) to methyl iodide is 1:2-5.
[0027] In one embodiment of the present invention, in step (S2), during the reaction, the temperature is 30-60° C. and the time is 48-72 hours.
[0028] In one embodiment of the present invention, the post-processing is as follows:
[0029] The reactant was precipitated in ethyl acetate, and the obtained solid was then washed with deionized water to obtain a yellow solid: a crown ether-based poly(aryl-dimethylpiperidone) salt.
[0030] In one embodiment of the present invention, in step (S3), the crown ether-based poly(aryl-dimethylpiperidone) salt is dissolved in an organic solvent;
[0031] The usage ratio of the crown ether-based poly(aryl-dimethylpiperidone) salt to the organic solvent is 1 g: 25-45 mL.
[0032] In one embodiment of the present invention, in step (S3), the post-treatment is to remove the residual solvent, and the specific process is as follows:
[0033] After the film is cast, the first evaporation treatment, the second evaporation treatment and the vacuum drying treatment are carried out in sequence.
[0034] In one embodiment of the present invention, during the first evaporation treatment, the temperature is 50 to 70° C. and the time is 10 to 18 hours;
[0035] During the second evaporation treatment, the temperature is 80-100°C and the time is 10-18 hours;
[0036] During the vacuum drying process, the temperature is 100-120°C and the time is 20-24 hours.
[0037] In one embodiment of the present invention, in step (S4), the concentration of the KOH solution is 1 to 3 mol / L;
[0038] During the ion exchange process, the temperature is 70-90°C and the time is 10-20 hours.
[0039] The third object of the present invention is to provide a use of a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane in the preparation of a fuel cell and / or an alkaline electrolytic cell.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) The present invention can achieve ionization of the crown ether-based poly(aryl-methyl piperidone) through a one-step reaction, that is, quaternizing the nitrogen atom of piperidone with methyl iodide to obtain a cationic group, and the preparation process is simple;
[0042] (2) The introduction of hydrophilic crown ether in the present invention improves the ionic conductivity of the membrane, reduces the degradation of the membrane under alkaline conditions, and solves the problem that AEM has poor alkaline stability and is easily affected by OH. - Offensive issues;
[0043] (3) The present invention adds a cyclic crown structure to the main chain to maintain the rigidity of the polymer backbone, which is beneficial to improving thermal stability and mechanical properties.
[0044] The crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane of the present invention has high OH - Electrical conductivity (80℃, OH - Conductivity>100mS cm -1), high mechanical strength (tensile strength>35MPa, elongation at break>10%), high dimensional stability, good processability, and high stability in 1M KOH at 80°C (>500h). BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 A synthetic route diagram of the poly(aryl-methylpiperidone) polymer provided in this application;
[0046] Figure 2 is the hydrogen nuclear magnetic resonance spectrum of the crown ether-based poly(aryl-methylpiperidone) polymer;
[0047] Figure 3 The synthetic route diagram of poly (aryl-dimethylpiperidone) salt;
[0048] Figure 4 The sample properties of poly(aryl-dimethylpiperidone) salt;
[0049] Figure 5 is the hydrogen nuclear magnetic resonance spectrum of the crown ether-based poly(aryl-dimethylpiperidone) salt polymer;
[0050] Figure 6 is the OH of PFOP and PAFOP-n (PAFOP-50, PAFOP-70 and PAFOP-90) AEMs - Conductivity graph;
[0051] Figure 7 Swelling ratio (SR) diagram of PFOP and PAFOP-n (PAFOP-50, PAFOP-70 and PAFOP-90) AEMs;
[0052] Figure 8 The water absorption (WU) graphs of PFOP and PAFOP-n (PAFOP-50, PAFOP-70, and PAFOP-90) AEMs;
[0053] Fig. 9 Figure 2 is the alkaline stability graph of PFOP and PAFOP-n (PAFOP-50, PAFOP-70 and PAFOP-90) AEMs. DETAILED DESCRIPTION
[0054] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0055] The test methods used in the following examples are as follows:
[0056] Ion exchange capacity (IEC) test method: A self-supporting polymer membrane based on crown ether poly(aryl-dimethylpiperidone) salt is dried in a vacuum oven at 75°C and the mass is weighed to record the weight of the dry film. The membrane is soaked in 25 mL of 0.2 M NaNO3 solution for 6 hours, repeated three times, and the NaNO3 solution after ion exchange is collected. The indicator potassium chromate solution is added to the solution, and titrated with 0.01 M AgNO3 standard solution. When a brick-red precipitate appears and does not disappear after shaking, the titration is complete. Record the volume of AgNO3 solution consumed. The product of the concentration and volume of the AgNO3 solution divided by the mass of the dry film is the IEC.
[0057] Conductivity test: The electrochemical workstation used was produced by Shanghai Chenhua Instrument Co., Ltd., model CHI660E. The conductivity of the branched membrane at different temperatures was tested by the alternating current impedance method (EIS). The measured potential amplitude was 10mV. In order to reduce the error caused by the contact resistance to the measurement results, the resistance tested was the in-plane resistance of the membrane sample. In the experiment, the membrane was cut into a size of 40mm×10mm, placed in a fixture, and the fixture was placed in pure water. The test temperature ranged from 30℃ to 80℃, and the membrane resistance was tested every 10℃. It was necessary to keep warm for 1h before the test. Finally, the ionic conductivity σ of the sample was calculated according to the formula: σ=l / (wdR) where l is the length of the membrane between the electrodes (cm), w is the width of the membrane (cm), d is the thickness of the membrane (μm), and R is the measured membrane resistance (mΩ).
[0058] Alkaline fuel cell performance test: The instrument used is produced by Scribner Associates Co., USA, and the instrument model is 850e multi-range fuel cell test system, and the test is carried out in current mode. The test conditions are full humidification of H2 and O2, the test temperature is 60℃, 80℃, and the flow rate of H2 and O2 is 200mL / min.
[0059] Anion exchange membrane water electrolysis performance test: the anode is titanium felt loaded with IrO2, the cathode is carbon paper loaded with Pt / C, and the electrode area is 4cm 2 The electrolyte is 1M KOH. The MEA electrolytic cell is assembled. The test instrument is CHI660e, and the electrolytic cell is subjected to a linear voltammetric sweep test.
[0060] Tensile strength test: Instron M3300 electronic universal testing machine was used to test the dry film sample 5×0.5 cm, with a tensile rate of 5 mm / min.
[0061] Alkaline stability test: The prepared anion membrane was immersed in NaOH solutions of different temperatures and concentrations, and its conductivity was measured at the same time. The alkaline stability was analyzed by the change in the conductivity of the electrolyte membrane.
[0062] Unless otherwise specified, all reagents used are commercially available reagents, and all detection means and methods used are conventional detection means and methods in the art.
[0063] Example 1
[0064] This embodiment provides the preparation of a crown ether-based poly(aryl-dimethylpiperidone) salt (PAFOP-50) anion exchange membrane, which specifically includes the following steps:
[0065] (1) Synthesis of crown ether-based poly(aryl-methylpiperidone) (PAFOPip-50): Figure 1 As shown (in this embodiment, n = 50, x = 50), p-terphenyl (1.16g, 5.00mmol), dibenzo-18-crown ether-6 (1.81g, 5.00mmol) and N-methyl-4-piperidone (1.44mL, 12.0mmol) were added to 10mL of dichloromethane at room temperature. Then, trifluoroacetic acid (1.01mL, 13.5mmol) and trifluoromethanesulfonic acid (8.75mL, 90mmol) were added dropwise at 0°C and stirred for 8h. Finally, the obtained highly viscous dark blue solution was precipitated into 1MNaOH solution, and the solid product was washed three times with deionized water. The obtained white fibrous polymer (PAFOPip-50) was filtered and then vacuum dried at 60°C for 24 hours. By nuclear magnetic hydrogen spectrum ( Figure 2 ) demonstrated the achievement of crown ether-based poly(aryl-methylpiperidone).
[0066]
[0067] (2) Synthesis of crown ether-based poly(aryl-dimethylpiperidone) salt (PAFOP-50): Figure 3 As shown (in this example, n = 50, x = 50), PAFOPip-50 (2.00 g, 5.03 mmol) was dissolved in dimethyl sulfoxide, followed by the addition of iodomethane (3.0 mL, 15.0 mmol); then, the mixture was stirred at 72 ° C for 48 h. Finally, the mixture was precipitated into ethyl acetate, washed with deionized water several times, and dried under vacuum at 60 ° C to obtain a yellow copolymer (PAFOP-50) (as shown Figure 4 As shown). By H NMR spectroscopy ( Figure 5 ) proved that the crown ether-based poly (aryl-dimethylpiperidone) salt was obtained.
[0068] (3) Preparation and ion exchange of PAFOP-50 anion exchange membrane: PAFOP-50 (1 g) in (2) was dissolved in 30 mL of dimethyl sulfoxide. The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter membrane and the filtrate was cast on a clean glass plate to remove the residual solvent. The film was then carefully peeled off from the glass plate to obtain a self-supporting polymer membrane. The self-supporting polymer membrane was then placed in a KOH solution for ion exchange and washed under inert atmosphere to obtain a crown ether-based poly(aryl-dimethylpiperidone) salt (PAFOP-50) anion exchange membrane.
[0069]
[0070] Performance test of PAFOP-50 anion exchange membrane:
[0071] The test results show that the PAFOP-50 anion exchange membrane prepared in this example has an OH - The conductivity is 110.2mS·cm -1 (like Figure 6 The swelling ratio is 172.3% (as shown in Figure 7 As shown), the water absorption rate is 190.3wt% (as shown Figure 8 The tensile strength is 18.6MPa (as shown in Table 1), the elongation at break is 14.8% (Table 1), and the alkaline stability is maintained for 1012h in 80℃ and 1M KOH (as shown in Table 1). Fig. 9 The above results show that the homogeneous anion exchange membrane prepared in this embodiment has small swelling, suitable ion conductivity and anion exchange capacity, and good mechanical properties.
[0072] Example 2
[0073] This embodiment provides the preparation of a crown ether-based poly(aryl-dimethylpiperidone) salt (PAFOP-90) anion exchange membrane, which specifically includes the following steps:
[0074] (1) Synthesis of crown ether-based poly(aryl-methylpiperidone) salt (PAFOPip-90): p-terphenyl (2.09 g, 9.00 mmol), dibenzo-18-crown-6 (0.37 g, 1.00 mmol) and N-methyl-4-piperidone (1.44 mL, 12.0 mmol) were added to 10 mL of dichloromethane (DCM) at room temperature. Then, trifluoroacetic acid (1.01 mL, 13.5 mmol) and trifluoromethanesulfonic acid (8.75 mL, 90 mmol) were added dropwise at 0°C and stirred for 8 h. Finally, the obtained highly viscous dark blue solution was precipitated into 1 M NaOH solution, and the solid product was washed three times with deionized water. The obtained white fibrous polymer (PAFOPip-90) was filtered and then vacuum dried at 60°C for 24 h to prepare crown ether-based poly(aryl-methylpiperidone).
[0075]
[0076] (2) Synthesis of crown ether-based poly(aryl-dimethylpiperidone) salt (PAFOP-90): PAFOPip-90 (2.00 g, 5.03 mmol) was dissolved in dimethyl sulfoxide, followed by the addition of iodomethane (3 mL, 15 mmol); then, the mixture was stirred at 60 °C for 48 h. Finally, a yellow copolymer (PAFOP-90) was obtained by precipitation into ethyl acetate, washing with deionized water several times, and vacuum drying at 72 °C.
[0077] (3) Preparation and ion exchange of PAFOP-90 anion exchange membrane: PAFOP-90 (1 g) in (2) was dissolved in 30 mL of dimethyl sulfoxide. The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter membrane and the filtrate was cast on a clean glass plate to remove the residual solvent. The film was then carefully peeled off from the glass plate to obtain a self-supporting polymer membrane. The self-supporting polymer membrane was then placed in a KOH solution for ion exchange and washed under inert atmosphere to obtain a crown ether-based poly(aryl-dimethylpiperidone) salt (PAFOP-90) anion exchange membrane.
[0078]
[0079] Performance test of PAFOP-90 anion exchange membrane:
[0080] The test results show that the PAFOP-90 anion exchange membrane prepared in this example has an OH - The conductivity is 96mS·cm -1 (like Figure 6 The swelling ratio is 110.7% (as shown in Figure 7 As shown), the water absorption rate is 120.7wt% (as shown Figure 8 The tensile strength is 31.2MPa (as shown in Table 1), the elongation at break is 25.3% (as shown in Table 1), and the alkaline stability is maintained for 1600h in 80℃ and 1M KOH (as shown in Table 1). Fig. 9 The above results show that the homogeneous anion exchange membrane prepared in this embodiment has small swelling, suitable ion conductivity and anion exchange capacity, and good mechanical properties.
[0081] Example 3
[0082] This embodiment provides the preparation of a crown ether-based poly(aryl-dimethylpiperidone) salt (PAFOP-70) anion exchange membrane, which specifically includes the following steps:
[0083] (1) Synthesis of crown ether-based poly(aryl-methylpiperidone) (PAFOPip-70): p-terphenyl (1.162 g, 7.00 mmol), dibenzo-18-crown-6 (1.081 g, 3.00 mmol) and N-methyl-4-piperidone (1.44 mL, 12.0 mmol) were added to 10 mL of dichloromethane at room temperature. Then, trifluoroacetic acid (1.01 mL, 13.5 mmol) and trifluoromethanesulfonic acid (8.75 mL, 90 mmol) were added dropwise at 0°C and stirred for 8 h. Finally, the highly viscous dark blue solution was precipitated into 1 M NaOH solution, and the solid product was washed three times with deionized water. The white fibrous polymer (PAFOPip-70) was filtered and then dried in vacuum at 60°C for 24 h to obtain crown ether-based poly(aryl-methylpiperidone).
[0084]
[0085] (2) Synthesis of crown ether-based poly(aryl-dimethylpiperidone) salt (PAFOP-70): PAFO Pip-70 (2.00 g, 5.03 mmol) was dissolved in dimethyl sulfoxide, followed by the addition of iodomethane (3.0 mL, 15.0 mmol). Then, the mixture was stirred at 72 °C for 48 h. Finally, a yellow copolymer (PAFOP-70) was obtained by precipitation into ethyl acetate, washing with deionized water several times, and vacuum drying at 60 °C.
[0086] (3) Preparation and ion exchange of PAFOP-70 anion exchange membrane: PAFOP-70 (1 g) in (2) was dissolved in 30 mL of dimethyl sulfoxide. The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter membrane and the filtrate was cast on a clean glass plate to remove the residual solvent. The film was then carefully peeled off from the glass plate to obtain a self-supporting polymer membrane. The self-supporting polymer membrane was then placed in a KOH solution for ion exchange and washed under inert atmosphere to obtain a crown ether-based poly(aryl-dimethylpiperidone) salt (PAFOP-70) anion exchange membrane.
[0087]
[0088] Performance test of PAFOP-70 anion exchange membrane:
[0089] The test results show that the PAFOP-70 anion exchange membrane prepared in this example has an OH - Electrical conductivity: 100.8 mS·cm -1 (like Figure 6 The swelling rate is 127.2% (as shown in Figure 7 As shown), the water absorption rate is 140.2wt% (as shown Figure 8 The tensile strength is 31.2MPa (as shown in Table 1), the elongation at break is 25.3% (as shown in Table 1), and the alkaline stability is maintained for 1380h in 80℃ and 1M KOH (as shown in Table 1). Fig. 9 The above results show that the anion exchange membrane prepared in this embodiment has small swelling, suitable ion conductivity and anion exchange capacity, and good mechanical properties.
[0090] Comparative Example 1
[0091] This comparative example provides a preparation method of a poly(terphenyl-dimethylpiperidone) salt (PFOP) anion exchange membrane, which specifically includes the following steps:
[0092] (1) Synthesis of poly(terphenyl-methylpiperidone) (PFOPip): m-terphenyl (2.31 g, 10.00 mmol) and N-methyl-4-piperidone (1.2 mL, 10.0 mmol) were added to 10 mL of dichloromethane at room temperature. Then, trifluoroacetic acid (1.01 mL, 13.5 mmol) and trifluoromethanesulfonic acid (8.75 mL, 90 mmol) were added dropwise at 0°C and stirred for 8 h. Finally, the highly viscous dark blue solution was precipitated into 1 M NaOH solution, and the solid product was washed three times with deionized water. The white fibrous polymer (PFOPip) was filtered and vacuum dried at 72°C for 24 h to obtain crown ether-based poly(aryl-methylpiperidone).
[0093]
[0094] (2) Synthesis of poly(terphenyl-dimethylpiperidone) salt (PFOP): PFOPip (2.00 g, 5.03 mmol) was dissolved in dimethyl sulfoxide, followed by the addition of iodomethane (3.0 mL, 15.0 mmol). Then, the mixture was stirred at 60°C for 48 h. Finally, the mixture was precipitated into ethyl acetate, washed several times with deionized water, and dried in vacuo at 60°C to obtain a yellow copolymer (PFOP).
[0095] (3) Preparation and ion exchange of PFOP anion exchange membrane: PFOP (1 g) in (2) was dissolved in 30 mL of dimethyl sulfoxide. The polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter membrane, and the filtrate was cast on a clean glass plate to remove the residual solvent. The film was then carefully peeled off from the glass plate to obtain a self-supporting polymer membrane. The self-supporting polymer membrane was then placed in a KOH solution for ion exchange and washed under inert atmosphere to obtain a poly(terphenyl-dimethylpiperidone) salt anion exchange membrane.
[0096]
[0097] Performance test of PFOP anion exchange membrane:
[0098] The test results show that the OH- conductivity of the PFOP anion exchange membrane prepared in this comparative example is 89.6 mS·cm at 80°C. -1 (like Figure 6 As shown), the swelling rate is 75% (as shown Figure 7 As shown), the water absorption rate is 85wt% (as Figure 8 As shown), the tensile strength is 42.3MPa (Table 1), the elongation at break is 37.6% (Table 1), and the alkaline stability is maintained for 870h in 80℃ and 1M KOH (as shown Fig. 9 The results show that the performance of the anion exchange membrane prepared in Comparative Example 1 is significantly reduced compared with that in the examples. This shows that the introduction of crown ether can effectively form hydrogen ion-crown ether complexes, increase water absorption, and accelerate OH - conduction, alleviating the degradation of the membrane under alkaline conditions.
[0099] Table 1 Mechanical properties of PFOP and PAFOP-n AEMs at room temperature
[0100]
[0101] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the explanation of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane, characterized in that: It is composed of a compound of the structure shown in formula (I): Here, x is any integer from 1 to 99.
2. A method for preparing a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane as claimed in claim 1, characterized in that: The following steps are involved: (S1) dissolving dibenzo-18-crown-6, p-terphenyl, N-methyl-4-piperidone, trifluoromethanesulfonic acid and trifluoroacetic acid, mixing and reacting, and post-treating to obtain a crown ether-based poly(aryl-methylpiperidone); (S2) dissolving the crown ether-based poly(aryl-methylpiperidone) prepared in step (S1), mixing with methyl iodide and reacting, and post-treating to obtain a crown ether-based poly(aryl-dimethylpiperidone) salt; (S3) dissolving the crown ether-based poly(aryl-dimethylpiperidone) salt prepared in step (S2) and casting it into a film, and then post-treating it to obtain a self-supporting polymer film; (S4) placing the self-supporting polymer membrane prepared in step (S3) in a KOH solution for ion exchange, and washing to obtain a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane.
3. The method for preparing a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane according to claim 2, characterized in that: In step (S1), the molar ratio of dibenzo-18-crown-6 to p-terphenyl is 0-10:10-0; The molar ratio of the sum of the added amounts of dibenzo-18-crown-6 and p-terphenyl to the added amount of N-methyl-4-piperidone is 1:0.9-1.2; The molar ratio of N-methyl-4-piperidone to the trifluoroacetic acid is 1:0.8-1.2; The molar ratio of the N-methyl-4-piperidone to the trifluoromethanesulfonic acid is 1:8-12.
4. The method for preparing a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane according to claim 2, characterized in that: In step (S1), the reaction process is under the protection of an inert atmosphere, the temperature is 0 to 10° C., and the time is 6 to 15 hours.
5. The method for preparing a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane according to claim 2, characterized in that: In step (S2), the mass ratio of the crown ether-based poly(aryl-methylpiperidone) to methyl iodide is 1:2-5.
6. The method for preparing a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane according to claim 2, characterized in that: In step (S2), during the reaction, the temperature is 30-60° C. and the reaction time is 48-72 hours.
7. The method for preparing a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane according to claim 2, characterized in that: In step (S3), a crown ether-based poly(aryl-dimethylpiperidone) salt is dissolved in an organic solvent; The usage ratio of the crown ether-based poly(aryl-dimethylpiperidone) salt to the organic solvent is 1 g: 25-45 mL.
8. The method for preparing a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane according to claim 2, characterized in that: In step (S3), the post-treatment is to remove the residual solvent, and the specific process is as follows: After the film is cast, the first evaporation treatment, the second evaporation treatment and the vacuum drying treatment are carried out in sequence.
9. The method for preparing a crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane according to claim 2, characterized in that: In step (S4), during the ion exchange process, the temperature is 60 to 80° C. and the time is 10 to 20 hours.
10. Use of the crown ether-based poly(aryl-dimethylpiperidone) salt anion exchange membrane according to claim 1 in the preparation of a fuel cell and / or an alkaline electrolytic cell.